Clinical Predictors of Future Nonadherence in Inflammatory Bowel Disease. Issue 9 (11th July 2017) - Severs, Mirjam; Mangen, Marie-Josée J.; Fidder, Herma H.; van der Valk, Mirthe E.; van der Have, Mike; van Bodegraven, Ad A.; Clemens, Cees H. M.; Dijkstra, Gerard; Jansen, Jeroen M.; de Jong, Dirk J.; Mahmmod, Nofel; van de Meeberg, Paul C.; et al.
Abstract : Background: Nonadherence to medical therapy is frequently encountered in patients with inflammatory bowel disease (IBD). We aimed to identify predictors for future (non)adherence in IBD. Methods: We conducted a multicenter prospective cohort study with adult patients with Crohn's disease (CD) and ulcerative colitis (UC). Data were collected by means of 3-monthly questionnaires on the course of disease and healthcare utilization. Medication adherence was assessed using a visual analogue scale, ranging from 0% to 100%. Levels <80% were considered to indicate nonadherence. The Brief Illness Perception Questionnaire was used to identify illness perceptions. We used a logistic regression analysis to identify patient- and disease-related factors predictive of nonadherence 3 months after the assessment of predictors. Results: In total, 1558 patients with CD and 1054 patients with UC were included and followed for 2.5 years. On average, 12.1% of patients with CD and 13.3% of patients with UC using IBD-specific medication were nonadherent. Nonadherence was most frequently observed in patients using mesalazine (CD), budesonide (UC) and rectally administrated therapy (both CD and UC). A higher perceived treatment control and understanding of the disease were associated with adherence to medical therapy. Independent predictors of future nonadherence were age at diagnosis (odds ratio [OR]: 0.99 per year), nonadherence (OR: 26.91), a current flare (OR: 1.30) and feelings of anxiety/depression (OR: 1.17), together with an area under the receiver-operating-characteristics curve of 0.74. Conclusions: Lower age at diagnosis, flares, feelings of anxiety or depression, and nonadherence are associated with future nonadherence in patients with IBD. Altering illness perceptions could be an approach to improve adherence behavior.